TIMING OF INOCULATION WITH SELECTED WINE BACTERIA ON THE KINETICS OF MALOLACTIC FERMENTATION AND SENSORY PROPERTIES OF SYRAH WINES FROM THE REPUBLIC OF NORTH MACEDONIA - Goran Milanov; Sibylle Krieger-Weber; Anthony Silvano; Ann Dumont; Dushko Nedekovski (MACEDONIAN ACADEMY OF SCIENCES AND ARTS, 2020)
To improve the quality of the wine the use of selected strains of lactic acid bacteria become regular and important tool in modern wine making practice. As a result of metabolic activity of the lactic acid bacteria in the fermentation process the wines acidity is reduced and the wines flavour is more shaped. For the study four commercial LAB strains form the producer Lallemand were used in the fermentation of Syrah grapes: Lalvin VP41, O-MEGA, ML-Prime, PN4. The objective of this study was to determine the sensorial impact between co-inoculation and sequential application of four different lactic acid bacteria strains. From the obtained results co-inoculation samples resulted in higher level of esters and higher fruit intensity. Some strains contributed to more freshness and varietal characters of the wines and other increased the wine mouthfeel and red berry flavours.
Keywords: Syrah grapes co-inoculation; lactic acid bacteria; kinetics; sensorial impact